Study of Full-body Virtual Embodiment Using noninvasive Brain Stimulation and Imaging - Škola, Filip; Liarokapis, Fotis (My University, 2021)
The sense of embodiment in virtual reality is a strong case of body ownership illusion, effectively allowing humans to experience the ownership of a modified, or a completely different body. Virtual embodiment has captured the attention of researchers in various fields, with applications far beyond computer science. Despite the promising applications, little is known about the neural mechanisms behind full-body virtual embodiment. This study investigates the influence of anodal transcranial direct current stimulation of the brain area linked to processing of the bodily self (right temporoparietal junction) to the subjective strength of virtual embodiment and its main constituents, using within-subject experimental design with sham-controlled stimulation. Virtual embodiment was studied using questionnaires, accompanied by brain signals gathered using EEG. Our results suggest that stimulation did not affect the sense of ownership toward the virtual avatar. Borderline strengthening of the perceived sense of agency toward the avatar’s actions was found in the sessions with stimulation.
Keywords: Virtual embodiment; Anodal transcranial